ANALISIS PENENTU PENDAPATAN PEDAGANG KAKI LIMA DI KOTA JEMBER (PENDEKATAN PRESPEKTIFDEMOGRAFI DAN SOSIAL EKONOMI) - Istatuk Budi Yuswanto (BALANCE: Economic, Business, Management and Accounting Journal, 2007)
The ammount of PKL onJemberCityalways increase continously every time. It caused by a lot of  unemployment becouse of economic crisis that not end yet. Beside that excistency of it help customer expesially low income to get their need. It  was needed to see the PKL problem as a true contex. It is  the problem of  increasing of their whealth of life. The goal of this research are to know demographic & social economic characteristic of PKL and also to know  the enfluence of  amount of work hour, working capital and  experience as PKL to PKL Income on Jember City. The technik sampling is random sampling, all of samples are 100 respondent.  Analysis data is discriptive and analysis statistic called multiple regression analysis. The result of the reasearch show that  45 % of PKL are 35-44 years old. Most of them  have low education. and also 38 % of them get income between Rp 30.000- Rp 39.000. Simoultantly and partially all independent variable (amount of work hour, working capital and  experience as PKL) have a significant effect to PKL Income onJemberCity.